UPAYA MENINGKATKAN PENGUASAAN KOSAKATA BARU MENGGUNAKAN MODEL CTL (CONTEKSTUAL THEACHING AND LEARNING) DI KELAS IV SDN SUKODONO I. - Erin Anggita Putri; Delia Indrawati; Agustin Indah K (CV. ADIBA AISHA AMIRA, 2023)
Education is a process that is carried out with awareness, which in everyday human life is timeless by what is called learning. In achieving learning goals, education has a very important role in human life. In the learning process it is also necessary to increase vocabulary in order to broaden horizons. This research is included in Classroom Action Research (CAR) using the Contextual Teaching and Learning (CTL) learning model which is a contextual learning process that aims to relate to the behavior of everyday life. This research was conducted in class IV of SDN Sukodono I. Students' mastery of new vocabulary increased after using the Big Indonesian Dictionary as a guide in finding the meaning of words. This increase is known from the evaluation at the end of learning with the completeness of student activity sheets. It can be proven from the results of the students' work, 19 out of 21 students have completed the work well. 2 students have not completed. The application of the CTL (contextual teaching and learning) model succeeded in helping to improve students' vocabulary mastery in learning Indonesian. This can be seen from the results of observations in cycles I and II which show an increase in each cycle.